Establishing the relationship between logistics complexity and supply chain objectives and decision areas in large companies operating in Brazil - Wanke, Peter (2010)
This paper reports an attempt to explore the relationships between logistics complexity and supply chain management (SCM) objectives and decision areas in large manufacturing companies operating in Brazil. Literature review is conducted, followed by survey research data (using a sample of 108 large companies operating in Brazil) analysis using cluster analysis, factor analysis and binary logistic regression. Results suggest that the level of logistics complexity of companies is a driver of management choices in supply chain objectives and decision areas, confirming our initial proposition that a contingency approach for supply chain management would be more appropriate than the "best practice" one. At the end of the article some further conclusions are drawn and opportunities for further research are discussed.